Why and Under What Contextual Conditions Do Early‐Maturing Girls Develop Problem Behaviors?. (16th July 2014) - Skoog, Therése; Stattin, Håkan
Abstract Researchers have proposed several theoretical models to account for the well‐established link between pubertal timing and social adjustment. The early models are general and pay little attention to mechanisms or contextual conditions, while newer models concentrate on interpersonal and contextual conditions. A recent theoretical approach—combining peer‐socialization and contextual‐amplification models—seeks to specify the theoretical mechanisms involved in the peer‐socialization explanation of the link between girls' early maturation and problem behavior, on one hand, and the contextual conditions during which peer socialization are likely to occur, on the other. Findings from our empirical studies on micro‐ and macrocontextual levels support this integrative approach. Models of how puberty affects behavior should recognize the social embeddedness of adolescents' behaviors, and should therefore be contextual.